Acids and bases - Lines, Jeremy; Video Education Australasia (Australia : Video Education Australasia, 2005)
Explains the early theories of Arrenhuis and Lowry Bronsted , Valence structures , exposed proton's and proton transfer , diprotic and tripotic acids linked to structures . The PH scale , conjugate pairs and standards reactions are all covered
Executive producer , Mark McAuliffe ; writer , associate producer Simon Garner ; camera , Michael Henry ; sound , Wayne Martin
Featuring , voice over : John Osborne
For middle secondary to senior secondary students
Keywords: Acids; Bases (Chemistry); Chemistry reactions